Analysis of The Improvement of Cone Machine Using Overall Equipment Effectiveness Method (OEE) - Julius Mulyono; Chatarina Dian Indrawati; Peter Rhatodirdjo Angka; Andrew Joewono (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2026)
The cone machine is the main machine, which is used to produce the cone for ice cream.  So, it is important for measuring the effectiveness of the machine. Overall Equipment Effectiveness (OEE) is one of method to determine the machine effectiveness. The calculation results that the cone machine effectiveness is still under the ideal standard of Overall Equipment Effectiveness, the percentage of effectiveness is 73.85%, percentage of availability rate is 91.55%, performance rate is 82.56%, and quality rate is 97.61%. The ideal OEE standard for manufacturing is 85%; while for food products it is 64%. This figure was adopted by this company. Meanwhile, using fishbone diagram, there are four factors that affect the productivity of cone production, that is, human, machine, method, and material (raw material). Improvements that are needed to be done are conducting training for the machine operators, and using better machine component, i.e. baking plate bearing components.